Gerstmann Syndrome in Adult Ukrainian Woman - Orlova, Nataliia; Shkliar , Mykhailo; Tarasov, Volodymyr (Psychosomatic Medicine and General Practice, 2021)
Background. During the screening phase of the study, we observed a middle-aged woman with a rare disorder known as Gerstmann’s syndrome. The woman showed four important neuropsychopathological symptoms that describe this disturbance. Methods. To assess the woman’s status, we used physical, psychiatric, psychopathological and neurological examinations, laboratory tests interpretation, retrospective analysis of the hospital sheet chart and literature search. Results. A 33-year-old East European woman from Ukraine has been suffering from acalculia since age six, digital agnosia, confusion of left-right orientation, and writing disturbances. She is lifelong right-hand dominant person and somebody in her family suffered from mental illness. She used to be successfully treated for anxiety and obsessions. She does not use any illicit drugs and denies alcohol use or abuse. The woman had never smoked cigarettes. Physical examination, CBC, complex metabolic panel, endocrine tests were within the age range. CT and MRI scans were common. Rheoencephalography revealed signs of moderate changes in venous outflow in the carotid basin on the left. We detected the most important psychopathological and neurological findings in mental health examinations. During assessment the woman was unable to perform simple arithmetic calculations. That is a crucial symptom, well known as a term an acalculia. Digital agnosia as the inability to identify or point to her own or someone else’s fingers was present as well. Also, she had left-right disorientation - an inability to distinguish between right and left, and mild writing disturbance - decreasing of the capability to express thoughts in writing. In addition, she had demonstrated constructional apraxia by performing the clock drawing test. Conclusions. We brought to light a rare syndrome in Ukrainian woman. The incidence of that syndrome in the general population has not yet been known. We found all four symptoms from a tetrad as a result of general brain damage with learning disabilities but some of the symptoms were mild. It is believed that some of them diminishing in adults over time.